Pain mediator NGF improves chondrocyte extracellular matrix synthesis via PI3K/AKT pathway - Mengling Wang; Jie Lian; Maoqing Ye; Bingchen An (Journal of Orthopaedic Surgery and Research)
Abstract Objectives Nerve growth factor (NGF) is a key mediator in osteoarthritis pain signaling. Clinical studies revealed that anti-NGF antibodies are often accompanied by progressively worsening cartilage degeneration, although they exhibit significant analgesic effects. However, the relationship between NGF expression and cartilage destruction remains unclear. Our study aimed to investigate the effects of NGF on chondrocytes and to elucidate the underlying mechanisms involved. Methods The ATDC5 cells were induced to differentiate into chondrocytes and stimulated with NGF at different concentrations (0.5–10 ng/mL). The cell counting kit-8 assay (CCK-8) was used to measure the effects of NGF on chondrocyte proliferation. Chondrocytes were subsequently stimulated with varying doses of NGF to identify the expression levels of the extracellular matrix. Chondrocytes were pretreated with GNF5837 (a tropomyosin receptor kinase A inhibitor) or LY294002 (a phosphoinositide 3-kinase inhibitor) before exposure to 5 ng/mL NGF to analyze associated signaling pathways. Western blotting and immunofluorescence staining were employed to analyze expression of related proteins. Results Alcian blue, toluidine blue staining, and type II collagen immunofluorescence staining demonstrated that ATDC5 cells differentiated into functional chondrocytes after 14 days of chondrogenic induction. The CCK-8 assay confirmed that cell proliferation was unaffected. NGF (0.5–5 ng/mL) was found to enhance chondrocyte matrix synthesis in a dose-dependent fashion, particularly in the expression of aggrecan, type II collagen, Sox9, and through the activation of the PI3K/AKT signaling pathway. The highest promoting effects were exhibited at 5 ng/mL of NGF. Further analysis indicated that GNF5837 (TRKA inhibitor) or LY294002 (PI3K inhibitor) could reverse the protective effects of NGF on chondrocyte matrix synthesis. Conclusion Our study identified a potentially beneficial role of NGF at concentrations of 0.5–5 ng/mL in chondrocytes, enhancing extracellular matrix synthesis, with significant involvement of the PI3K/AKT signaling pathway in this process.